Covid-19 Related Disruption of Out-Patient Services: An Opportunity for Integrating Telemedicine into Clinical Practice in Public Hospitals in Nigeria (African Journal of Biomedical Research, 2020)
The number of cases of COVID-19 disease has rapidly escalated worldwide causing widespread socio-economic disruptions as goverrnments enforced strict movement restriction (lockdown) measures to contain its spread. Because hospitals were also considered high risk areas for transmission of the disease, several measures were introduced in hospitals worldwide, Nigeria inclusive, to limit non-essential visits to the hospitals and reduce healthcareworker-patient interractions to only what is necesssary. Such measures included the complete or partial closure of Outpatient departments in many public hospitals with the attendant deleterious effects of disruption of patients’ care plans, lack of access to physician attention, counselling and prescription refills.With the easing of the lockdown nationwide, most public hospitals yet to return to pre-lockdown free- flowing patient care arrangements especially in the outpatient clinics either due to reduction in total number of patients accommodated in new physical-distancing inspired arrangements or delays in accessing care due to unwieldy triage processses. This has led to significant difficulties for patients. In the face of this, and the spate of rising cases of COVID-19 infections in Nigeria and worldwide, we propose that Telemedicine should be introduced into outpatient consultations in Nigeria. We propose a model for involving Telemedicine in the outpatient care of patients side-by-side the usual physical consultation. Our model proposes telesmart triage and identification of patients who may benefit from Teleconsultation so as to reduce the pressure on healthcareworker-patient interraction. This will reduce the risk of transmission of COVID-19 to healthcareworkers and reducing the cost of personal protective equipment.